A INTERVENÇÃO EDUCATIVA COM ACOMPANHANTES DE PACIENTES: UM RELATO DE EXPERIÊNCIA - Amthauer, Camila; Falcade, Bruna L.; Begnini, Danusa; Cogo, Silvana B.; Gasparini, Danieli (Salão do Conhecimento, 2013)
Resumo